THE DIFFERENCE BETWEEN THE ALTMAN Z-SCORE AND SPRINGATE MODELS IN ANALYZING THE BUSINESS SUSTAINABILITY OF PT. SRI REJEKI ISMAN TBK - Sinaga, Mahaitin H; Tarigan, Wico Jontarudi (Program Studi Akuntansi Universitas Simalungun, 2024)
The purpose of this study was to determine the difference between altman z-score and springate in predicting going concern and find out which model has the highest level of accuracy between the altman z-score and springate models at PT Sri Rejeki Isman Tbk. The type of data used by researchers in this study is the type of quantitative and qualitative. Data collection technique is with documentation. The data analysis techniques used are quantitative descriptive methods and inductive methods. The results of the calculation of the original altman z-score method from the 2019-2023 period show that PT Sri Rejeki Isman Tbk is in a state prone to bankruptcy in 2019 - 2020 and experienced bankruptcy in 2021 and then in 2022 - 2023 again in a state prone to bankruptcy. The result of the altman z-score and zmijewski models calculations from the period 2019 - 2023 show that PT Sri Rejeki Isman Tbk has a slight difference in the calculation results and interpretation where the altman z-score model shows that PT Sri Rejeki Isman Tbk is in a position prone to bankruptcy in 2019 – 2020 then in 2021 experienced bankruptcy and returned to bankruptcy prone in 2022-2023. Meanwhile, by using the Zmijewski model throughout the years 2019 - 2023, PT Sri Rejeki Isman Tbk is in an unhealthy state and has experienced bankruptcy